(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
Hot food ( soups, sauces, hot drinks, main dishes and side dishes ) in distribution temperature should be 60-65°C it is necessary Hot food temperature this from the indicator when it decreases of microflora intensive to growth take to come, on the contrary Hot food temperature this from the indicator high if the children mouth space to burn take coming can.